The impact of increased import competition from the People's Republic of China on income inequality and household welfare in Viet Nam - Matthias Helble; Trang T. Le; Trinh Quang Long (Asian Development Bank Institute (ADBI), 2018)
This paper examines the surge of imports from the PRC to Viet Nam from 2000 to 2014 in order to evaluate the effects of increased exposure to trade with the PRC on income inequality and household welfare in Viet Nam. Using household level data from the Viet Nam Household Living Standard Survey and combining it with measures of trade exposure, we find that increased imports led to a fall in inequality at the provincial and district level. We distinguish between intermediate and final goods and find similar results. In order to better understand the relative gains and losses across income groups, we apply a quantile regression approach. Our results indicate that increased imports were more often positively correlated with household income for households located in the lower quantiles. In contrast, for households in the upper quantiles the correlation is either negative or less pronounced.
Keywords: F1; D63; 330